Inclusive digital world: examining access, affordability and ability in Malaysian underserved community/ Jasber Kaur GS and Halimatus Saadiah Ab Karim - GS, Jasber Kaur; Ab Karim, Halimatus Saadiah (Faculty of Information Management, 2024)
Digital inclusion is a pressing global challenge and Malaysia is no exception. Access, affordability and digital ability remains a challenge in achieving digital inclusion in Malaysia. Previous studies have only focused either one or two of these three factors at a time, leading to the absence of a comprehensive digital inclusion model. Additionally, there is dearth of study on the topic of digital inclusion among the lower income group. The purpose of this study is to investigate the factors that contribute to digital inclusion within the B40 community and to further investigate the digital gender gap that exists within that community. The study adopts quantitative research paradigm utilising survey questionnaire as data collection method. Questionnaire items were adopted from past research works consisting of three constructs; access, affordability, and digital ability, as measurement tool for digital inclusion model. Survey was distributed and administered physically in the presence of researcher and community leader at Pusat Perumahan Rakyat (PPR) Kerinchi which is located in Kuala Lumpur city centre. Among the three factors, study findings shows that affordability is the main barrier for the B40 community to be digitally included as digital technologies and cost of internet are becoming too costly. Consequently, this has an effect on their accessibility to the internet as a result of the fact that the likelihood of them possessing devices and purchasing internet and mobile data plans is significantly reduced due to their fairly low income. The findings of the survey also showed that there is no difference between men and women regarding their level of perceived digital inclusion within the community. The study findings reveal the importance of a holistic approach to digital inclusion in Malaysia. The interplay between access, affordability and digital ability emphasizes the need for collaborative efforts among government, civil society, academia and industry stakeholders to create an inclusive digital ecosystem